Contributing factors for menopausal symptoms after surgical staging for endometrial cancer. Issue 5 (May 2016) - Matsuo, Koji; Gualtieri, Marc R.; Cahoon, Sigita S.; Toboni, Michael D.; Machida, Hiroko; Moeini, Aida; Hasegawa, Kosei; Shoupe, Donna; Roman, Lynda D.
Abstract: Objective: The aim of the study was to examine contributing factors associated with developing menopausal symptoms after surgical staging in women with endometrial cancer. Methods: This is a retrospective study examining patients with endometrial cancer who were premenopausal at the time of hysterectomy-based surgical staging including bilateral oophorectomy between January 2000 and October 2013. Cox proportional hazard regression model was used to evaluate demographics, medical comorbidity, liver function tests, tumor factors, and medication history for menopausal symptoms. Results: There were 269 premenopausal women who were eligible. Mean age was 44.5 years, and the majority had endometrioid histology (91.1%), grade 1 tumor (60.2%), and stage I disease (65.8%). Postoperatively, 73 (27.1%) women developed menopausal symptoms, with hot flushes (20.1%) being the most common symptom followed by night sweats (4.1%). On multivariate analysis, younger age was independently associated with increased risk of developing menopausal symptoms (hazard ratio per unit 0.91, 95% CI 0.88-0.94, P  < 0.01). In addition, lower albumin level remained an independent predictor for decreased risk of developing menopausal symptoms (hazard ratio per unit 2.16, 95% CI 1.19-3.93, P  = 0.012). Lower albumin level was associated with medical comorbidity (hypertension and diabetes mellitus), use of antihypertensive/glycemic agents (angiotensin-converting enzyme inhibitors or receptor blocker, hydrochlorothiazide, sulfonylurea, and insulin), aggressive tumor (high cancer antigen 125 level, nonendometrioid histology, and advanced stage), and abnormal liver function (high alkaline phosphatase level and low total protein level; all, P  < 0.05). Conclusions: Assessing albumin level, medical comorbidity, and medication type for the development of postoperative menopausal symptoms is a valuable step in the preoperative management of women with endometrial cancer. Abstract : Supplemental Digital Content is available in the text